Moving towards sustainable coasts: A critical evaluation of a stakeholder engagement group in successfully delivering the mechanism of adaptive management. (April 2018) - Creed, R.; Baily, B.; Potts, J.; Bray, M.; Austin, R.
Abstract: It is widely recognized that there is a need for engagement between stakeholders to establish locally accepted strategies for sustainable coastal management solutions around the world. Adaptive management approaches have emerged as one of the preferred mechanisms in coastal zone management. Central to the application of adaptive management is the effective engagement of stakeholders to encourage participatory decision-making. There are relatively few studies which have analysed the effectiveness and dynamics of stakeholder groups to establish sustainable adaptive management in practice, and identify what opportunities and challenges can arise from such collaborative approaches. This research critically evaluates stakeholder engagement in the adoption of adaptive management at East Head, England. The study has identified significant issues and opportunities that have arisen throughout the decision-making process. It has found that a major challenge has been to achieve acceptance of the mechanism of adaptive management, particularly in relation to aspects of uncertainty. However, it is of critical note that the advisory group in question has become a valuable vehicle in bringing together key stakeholders throughout all stages of the adoption of the adaptive management approach. It is suggested that this approach, has gradually reduced conflict through building knowledge, gaining trust and ultimately achieving acceptance. A widely applicable management model and recommendations for best practice are presented as derived from the views of the advisory group itself. This model has the potential to develop a more dynamic, holistic and sustainable approach to coastal governance both in the UK and at other locations further afield.